2019
DOI: 10.1093/cid/ciz866
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Prophylaxis for Bacterial Sexually Transmitted Infections

Abstract: Abstract Bacterial sexually transmitted infections (STIs) have been increasing over the past 2 decades in gay, bisexual, and other men who have sex with men. With the widespread use of early human immunodeficiency virus (HIV) treatment, which virtually eliminates transmission risk, and the availability of HIV pre-exposure prophylaxis, there have been attitudinal changes regarding HIV infection with resultant increases in sexual contact and declines in condom use.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 41 publications
1
90
0
Order By: Relevance
“…Although this has been shown to potentially decrease the incidence of syphilis and chlamydia, follow‐up has been short and there is a risk of promoting development or acquisition of tetracycline resistance in STI bacteria and the microbiome more generally. Additional studies in different settings and with longer follow‐up are required before this prophylactic treatment can be recommended 144 …”
Section: Special Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this has been shown to potentially decrease the incidence of syphilis and chlamydia, follow‐up has been short and there is a risk of promoting development or acquisition of tetracycline resistance in STI bacteria and the microbiome more generally. Additional studies in different settings and with longer follow‐up are required before this prophylactic treatment can be recommended 144 …”
Section: Special Considerationsmentioning
confidence: 99%
“…Partner notification may have to be extended to 2 years for patients with secondary syphilis associated with clinical relapse or in early latent syphilis. Longer time periods may be required in those with late latent and tertiary syphilis 144 46–60% of traced sexual contacts, including pregnant women, of patients with early syphilis are likely to be infected 146 …”
Section: Special Considerationsmentioning
confidence: 99%
“…In the same way that antiretroviral therapy is used to prevent HIV infection in the forms of PrEP and post-exposure prophylaxis (PEP), there is evidence that antibiotics for STI treatment could be used to prevent STIs. Doxycycline is a tetracycline antibiotic, which is commonly used as primary prevention (pre-and post-exposure prophylaxis) for several infectious diseases (4) and bacterial STIs treatment, but more recently has been assessed by studies as a preventative intervention for STIs (5). A sub-study of the ANRS-IPERGAY trial in France among 232 high risk men who have sex with men (MSM) using HIV PrEP, showed that Doxycycline post-exposure prophylaxis (Doxy-PEP) following condomless sex, was effective in reducing incidence of a first episode of chlamydia and syphilis but not gonorrhoea (6).…”
Section: Introductionmentioning
confidence: 99%
“…Daily doxycycline would also have the benefit of treating latent syphilis given its status as a second‐line agent against T. pallidum [25]. Multiple trials are currently ongoing to assess the utility of doxycycline prophylaxis among high‐risk populations such as men who have sex with men [26]. Our data further identify fishing communities as another important target group to consider for such interventional studies.…”
Section: Discussionmentioning
confidence: 97%